solve by completing the square

First thing you have to do is

(x-3)^2 = x^2-6x+9

x^2-6x+2 = (x^2-6x+9) - 7= (x-3)^2 - 7 = 0

(x-3)^2 = 7

x-3 = sqrt(7)

x = 3 +- sqrt (7)

solve by completing the square

Tutors, please sign in to answer this question.

First thing you have to do is

(x-3)^2 = x^2-6x+9

x^2-6x+2 = (x^2-6x+9) - 7= (x-3)^2 - 7 = 0

(x-3)^2 = 7

x-3 = sqrt(7)

x = 3 +- sqrt (7)

Randy R.

Middle and High School Math, Chemistry, General Science

Nutley, NJ

4.9
(126 ratings)

Daniel H.

Harvard & Law School Graduate - Master Tutor for Tests/Academics

New York, NY

4.8
(33 ratings)

Noah C.

An Expert, Passionate SAT Instructor

New York, NY

5.0
(67 ratings)